Teachback with Google Expeditions: investigating student practices and changes in perceptions in L2 spoken Accuracy and Fluency - Demetriou, Alan Andrea (Language Center, Cyprus University of Technology, 2018)
The purpose of this qualitative research was to study how Teachback, an innovative communication technique used in the Healthcare sector to communicate effectively with patients (AHRQ, 2014), is adapted by the students/learners when used with an emerging technology, Google Expeditions, an instructor-led Virtual Reality field trip (Howard, 2016), in an L2 classroom setting. Google Expeditions or Teachback had not yet been applied in a language teaching classroom environment, indicating a gap in the literature. The dissertation set three Research Questions at its foundation. It first wanted to see how Teachback with Google Expeditions is applied by students in English as Foreign Language classroom; secondly the study wanted to see whether perceptions regarding speaking Accuracy and Fluency changed after the application of the Teachback sessions; thirdly, the study wanted to see how the participants experienced Teachback with Google Expeditions in an EFL setting. Qualitative data was collected from five L1 Greek speakers during five recorded sessions through questionnaires, classroom observations and audio/visual recordings. The data analysis concluded that during its application, Teachback practices had been adapted according to student needs. Perceptions regarding speaking Accuracy and Fluency had changed but only slightly. Lastly, the data revealed that the study’s participants experienced Teachback with Google Expeditions positively. Future studies in the field may want to consider using larger samples as well as conducting more Teachback sessions which would brings greater validity to the future study’s findings.
Keywords: Teachback; Google Expeditions; Virtual Worlds; Speaking Skills; Accuracy; Fluency; Teachback google expeditions; Εικονικοί κόσμοι; Ευφράδεια λόγου; Ακρίβεια λόγου